STK11 rs2075604 Polymorphism Is Associated with Metformin Efficacy in Chinese Type 2 Diabetes Mellitus. (9th July 2017) - Li, Qingchu; Li, Cuilin; Li, Haoyun; Zeng, Liu; Kang, Zhiqiang; Mao, Yu; Tang, Xinyue; Zheng, Panpan; He, Li; Luo, Fang; Li, Zhi
Abstract : Metformin is a classical oral antidiabetic drug, often recommended to be the first-choice treatment of type 2 diabetes mellitus (T2DM). Based on the previous research on STK11 and diabetes, we aimed to investigate the distributive characteristic of STK11 rs2075604 polymorphism and the potential influence of STK11 rs2075604 polymorphism on metformin efficacy among Chinese T2DM patients. There was no significant difference between T2DM patients ( G = 64.8%, T = 35.2%) and healthy subjects ( G = 62.7%, T = 37.2%) in STK11 rs2075604 genotype and allele frequencies. After 12 weeks of treatment, 62 patients were defined as the responders and 32 patients as nonresponders according to the decrease of HbA1c level. And the GT + TT genotype in STK11 rs2075604 can decrease HbA1c level more significantly than the GG genotype. Furthermore, the allele frequency of T in the STK11 rs2075604 was higher in the responders than the nonresponders (43.55% versus 26.56%). The T allele in the STK11 rs2075604 had a 2.133 times great chance of responding to metformin treatment. In conclusion, this study suggested that the STK11 rs2075604 genetic polymorphism was significantly associated with metformin efficacy in Chinese T2DM patients and the carriers of the T allele may gain a better therapeutic metformin efficacy compared with the G allele. This trial is registered with clinical study registration number NCT03155087 .